2012
DOI: 10.1088/0963-0252/22/1/015018
|View full text |Cite
|
Sign up to set email alerts
|

Normal regime of the weak-current mode of an rf capacitive discharge

Abstract: This paper studies the normal and abnormal regimes of a weak-current rf discharge in ammonia, nitrogen, hydrogen and N 2 O for the rf electric field frequencies of 13.56 and 27.12 MHz. We reveal that only the abnormal regime of burning is observed at low pressures when the current growth is accompanied by an rf voltage increase while the surface of the electrodes is completely covered with the discharge. The normal regime occurs at higher gas pressures when the current growth is due to the increase in the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(76 reference statements)
3
6
0
Order By: Relevance
“…Our data for large pressure values agree with the conclusion of paper (Lisovskiy et al 2013), where it was demonstrated that the normal current density effect in the rf discharge in the N 2 O gas is best described by the model assuming the constant mean free path of N 2 O + ions in the near-electrode sheath. Note that conventionally the normal mode is observed in the rf discharge in N 2 O at the pressure values order of or above 1 Torr.…”
Section: Resultssupporting
confidence: 90%
“…Our data for large pressure values agree with the conclusion of paper (Lisovskiy et al 2013), where it was demonstrated that the normal current density effect in the rf discharge in the N 2 O gas is best described by the model assuming the constant mean free path of N 2 O + ions in the near-electrode sheath. Note that conventionally the normal mode is observed in the rf discharge in N 2 O at the pressure values order of or above 1 Torr.…”
Section: Resultssupporting
confidence: 90%
“…The RF capacitive discharge consists of two near-electrode sheaths (in which the positive space charge predominates), as well as a quasi-neutral plasma in between them (Figure ). , …”
Section: Resultsmentioning
confidence: 99%
“…The main difference between the cases of horizontal and vertical electrodes is that the voltage drop in the near-electrode sheath (its constant component) can reach hundreds and even thousands of volts, ,, while the dielectric walls of the discharge tube are under a floating potential relative to the plasma, the sign of which is usually negative, and the value is usually 3–5 electron temperatures and does not exceed 15–20 V. , Consequently, only relatively small NPs can be retained in the discharge plasma with vertically arranged electrodes (in the experiments described above, we saw particles with a typical diameter of up to about 400–600 nm), while larger particles must overcome a small electric field force and fall onto the tube wall. With horizontal electrodes, gravity is opposed by a much stronger electric field in the near-electrode sheath, and much larger particles can be retained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cathode phase, the electrons are swept out of the layer back into plasma. As a result, they acquire the energy with the appearance of peaks on the electron temperature plot near the boundaries of the layers [37][38]. On the contrary, the cooling phenomenon created by means of the electron density and the ground state of neon atoms, as well as the threshold ionization and excitation are weakening in the sheath thickness.…”
Section: With and Without Dielectricsmentioning
confidence: 99%